Enhanced Myeloid Leukocytes in Obese Children and Adolescents at Risk for Metabolic Impairment - Gállego-Suárez, Cecilia; Bulan, Ayse; Hirschfeld, Emily; Wachowiak, Phillip; Abrishami, Simin; Griffin, Cameron; Sturza, Julie; Tzau, Abigail; Hayes, Taryn; Woolford, Susan J.; Lumeng, Carey N.; Lee, Joyce M.; et al. (Frontiers in Endocrinology, 2020)
Objective: We aimed to examine if myeloid leukocyte profiles are associated with metabolic impairment in children and adolescents with obesity, and if sex, age, or race influence this relationship. Methods: 282 children ages 8-17 were evaluated. Predictor measures were absolute neutrophil counts (ANC), absolute monocyte count, monocyte subtypes and C reactive protein (CRP). Outcome variables were waist circumference, fasting glucose and insulin, HOMA-IR, HbA1c (%) and lipid profiles. Pearson correlation coefficients were used to determine associations between predictor and outcome variables. Wilcoxon two-sample tests were used to evaluate differences by sex. Results: CRP (p<0.0001), ANC (p<0.0018), and classical monocytes (p=0.05) were significantly higher in children with obesity. CRP, ANC and classical monocytes showed positive correlations with waist circumference, insulin, HOMA-IR and triglycerides. CRP was positively associated with ANC overall (p=0.05). ANC demonstrated positive correlation with monocytes (p<0.001). The associations between predictor and outcome variables were influenced by sex, race and age. Conclusions: CRP and myeloid leukocyte populations, specifically classical monocytes and neutrophils associate with both body composition and metabolic parameters in children with obesity suggesting that these cells may play a critical role in metabolic impairment. Race, gender and age interactions between monocytes and metabolic parameters were significant.